APPLICATION OF SOLUBLE AND IMMOBILIZED α - GALACTOSIDASE FROM ACINETOBACTER SP FOR DEGRADATION OF GALACTO-OLIGOSACCHARIDES IN COWPEAS - SIRISHA E,; RANJIT P,; LAKSHMI NARASU M, (International Journal of Pharma and Bio Sciences, 2017)
α-galactosidase purified from Acinetobacter sp. was immobilized in four different matrices- Calcium alginate, Gelatin, Agarose and k-Carrageenan. On comparative analysis, k-Carrageenan immobilized enzyme showed highest immobilization yield of 68% and storage stability for 30 days. Gelatin showed an immobilization yield of 57%. Soluble enzyme led to decrease of 84% in raffinose and 76% in stachyose concentration in cowpeas whereas k-Carrageenan immobilized enzyme led to decrease of 72% of raffinose and 54% of stachyose thereby decreasing the flatulence to greater extent.